Analysis of Motherhood Constellation among Adolescent Mothers With and Without Depressive Symptoms - da Silva Budzyn , Carine (2023)
This study analyzed the Motherhood Constellation in two young mothers (19 and 22 years old), with and without depressive symptoms. Through qualitative content analysis of the interviews, information was categorized according to four themes of this construct: life-growth, primary relating, support matrix, and identity reorganization. There were no differences between mothers in the first theme. In the others, despite the similarities with the asymptomatic mother, the young woman with depressive symptoms had difficulty to get involved with her baby, restricted social support, and an impasse related to the organization of her maternal identity and internal reorganization in the face of developmental demands. These findings indicate the need for attention to the mental health of young mothers during the complex process of becoming a mother.